Impact of Quality Assurance on Job Performance among Senior Secondary Schools Teachers in Minna Educational Zone of Niger State, Nigeria - Awwal , Ibrahim; Waziri, Fati Isa (International Journal of Educational Management, 2022)
This study is tagged “Impact of Quality Assurance on Job Performance among Senior Secondary Schools Teachers in Minna Educational Zone of Niger State, Nigeria”. Three research questions guided this this study which were is there impact of quality assurance on teachers’ use of instructional materials, is there impact of quality assurance on teachers’ use of pedagogies in teaching and is there Impact of quality assurance on teachers’ use of records in senior secondary schools in Minna Educational Zone Nigeria? Survey design was used. The population was 2762 with 279 sample. Multistage sampling technique was used with 20 self-designed structured-items questionnaire. Reliability was ascertained through pilot study via test re-test method and the two results were correlated using Pearson Product Moment Correlation Coefficient; 0.96 was obtained which implies the instrument was reliable. Mean was used to analyse the data. The study revealed that quality assurance enhances teachers’ ability to use, manage and maintain instructional materials in the school, enhances teachers’ use of teaching pedagogies and influence effective record keeping in the school. It was recommended that government should use quality assurance reports to enhance provision of instructional materials to promote quality teaching, principals should effectively and constantly supervise teachers to ensure appropriate use of teaching pedagogies and internal and external supervisors should constantly check to guide teachers’ use of records to promote effective management of senior school secondary schools in Minna Educational Zone of Niger State, Nigeria.